A giant solitary fibrous tumour of the liver: a case report - Roman, Jan; Vávra, Petr; Vávrová, Michaela; Židlík, Vladimír; Pelikán, Anton (Acta chirurgica belgica, 2023)
BACKGROUND: Solitary fibrous tumour of the liver is a rare mesenchymal tumour, occurring usually in women and with various symptomatology. The symptoms mostly result from pressure of the tumour mass on surrounding organs. Due to unknown biological behaviour and gradual increase of tumour volume, surgical resection is mostly the preferred treatment option. CASE: A 75-year-old woman with a history of endometrial cancer, presenting with an incidental finding of a liver mass, initially considered of infectious origin (either echinococcosis or cysticercosis). Further diagnostics did not clarify the aetiology, a surgical revision was rejected at the time. The subsequent follow-up was interrupted by the development of symptoms of gastrointestinal and renal obstruction, which led to a complete surgical removal of the tumour, sized 30 × 25 × 20 cm. A histopathological examination showed a CD34 and STAT6 positivity, leading to a diagnosis of a giant solitary fibrous tumour of the liver. The patient recovered well, without any signs of recurrence. CONCLUSION: The solitary fibrous tumour of the liver is a rare, often incidental finding. It is considered benign, but malignant growth was also reported. A gradual growth mostly results in pressure on other organs. A surgical resection is the treatment of choice. Transarterial embolization is another treatment possibility. Due to indeterminate malignant potential a regular follow-up is necessary, including tumour markers and imaging methods.
Keywords: Liver; Biomarkers, Tumor; lidé; Female; senioři; nádorové biomarkery; játra; Aged; Solitary Fibrous Tumors; transkripční faktor STAT6; STAT6 Transcription Factor; ženské pohlaví; solitární fibrózní tumory; Humans